LARP7 Suppresses Endothelial-to-Mesenchymal Transition by Coupling With TRIM28. Issue 9 (10th September 2021) - Liang, Xiaodong; Wu, Shuo; Geng, Zilong; Liu, Li; Zhang, Shasha; Wang, Shiyan; Zhang, Yan; Huang, Yu; Zhang, Bing
Abstract : Supplemental Digital Content is available in the text. Abstract : Rationale: Endothelial-to-mesenchymal transition (EndMT) is a fundamental biological process in which endothelial cells lose their endothelial characteristics and acquire mesenchymal properties. EndMT contributes to physiological organ development such as valvulogenesis and is associated with a number of deleterious pathologies such as organ fibrosis. Several signaling pathways of TGF-β (transforming growth factor β), BMP (bone morphogenetic protein) and inflammation have been shown to regulate EndMT. However, the transcriptional and epigenetic programs governing EndMT remains largely unclarified. Objective: To identify the transcriptional or epigenetic mechanisms underlying EndMT and EndMT-associated formation of cardiac valves. Methods and Results: We identified the LARP7 (La ribonucleoprotein domain family member 7), a RNAPII (RNA-binding protein regulating RNA polymerase II) pausing, was downregulated in 2 cytokine-induced EndMT models. LARP7 depletion with lentivirus-mediated shRNA transformed endothelial cells to mesenchymal morphology and induced the expression of the EndMT key regulator, SLUG. Specific deletion of LARP7 in the endocardium in inducible CDH5 CreERT2 ;LARP7 f/f mouse enhanced EndMT in the atrioventricular and outflow tract cushion as revealed by lineage tracing approach. ChIP-seq analysis showed LARP7 and TRIM28 (tripartite motif containing 28) which is an epigenetic repressor were colocalized at SLUG promoter. LARP7 directly interacted with TRIM28 and facilitated it loading to SLUG promoter and repressed its transcription through deacetylating the histones. More importantly, inducible knockout of LARP7 or TRIM28 in the endocardium accelerated EndMT, leading to the valvular hyperplasia, which was further aggravated by the double knockout of these 2 genes. Conclusions: The present study uncovers an orchestrated transcriptional and epigenetic mechanism by which LARP7 cooperates with TRIM28 to govern the EndMT and valvulogenesis.